Accessibility And Facilities As Determinants Of Gen Z Tourists' Interest In Returning To Cunca Wulang - Estikowati Estikowati; Lusiana Dominique Jempalu; Anisa Zuhria Sugeha (Jurnal Penelitian, 2025)
Tourism is a crucial industry that boosts economic development and enhances the well-being of communities close to tourist attractions. Despite its potential as a natural tourist destination, the Cunca Wulang waterfall in West Manggarai Regency, East Nusa Tenggara, is still hampered by its lack of amenities and accessibility. The purpose of this research is to determine how facilities and accessibility affect Gen Z tourists' desire to return to Cunca Wulang Waterfall. With a survey methodology, the research employs a quantitative strategy. Using the Slovin method, the sample size was determined to be 98 Gen Z tourist respondents. The information was gathered using a Likert scale-based survey, and then SPSS was used to do a multilinear regression analysis. According to the findings, facilities had no discernible impact on the desire to return, but accessibility had a beneficial and considerable impact. At the same time, however, accessibility and amenities were shown to have a considerable impact on the desire to return, with accessibility being the most influential factor. To sum up, the ease of getting to tourist attractions is a key element in persuading Gen Z tourists to return, while facilities still need to be upgraded to improve the tourist experience, even if they aren't as important in particular. Local authorities and tourism managers may utilize the findings of this study as a foundation for creating plans for the long-term development of tourism at Cunca Wulang Waterfall.